Investigation on the Current Status of Functional Movement Screen(FMS) for Male Specialized Football Athletes in Colleges and Universities - Wei , Yanqing; Chen , Yong (Scientific Journal of Technology, 2025)
Football is a high-intensity competitive sport that involves the shoulders, torso, and lower limbs of the body. During movement, various parts of the body engage in complex coordination to achieve movements such as footwork, foot frequency, sprinting, turning, and jumping. This sport requires athletes to have highly developed physical fitness and is often accompanied by sports injuries. The seven test movements in Functional Movement Screening (FMS) include the basic movement patterns of the human body. It is a measurement tool used to evaluate the quality of athletes’ movements and exercise risks. Based on the results, the training plan can be adjusted accordingly, and corrective training can be carried out to reduce exercise risks and improve athletic performance. At present, the application of this measurement tool in college football special athletes is relatively limited. Therefore, this article selects this group for research, with two research objectives: firstly, to understand the overall and sub scoring characteristics of FMS for male specialized football players in universities through testing, and secondly, to explore the relationship between FMS test results and athletes’ sports injuries. This study focuses on 18 male football students majoring in physical education from Lvliang University who participated in the Shanxi Province Campus Football League. Firstly, before the test, the subjects filled in a survey questionnaire about their training time and sports injury history within one year. Then, the functional movement quality of the subjects was tested using a functional movement screening kit. After the test, the distribution characteristics of the overall and sub item scores of the subjects’ functional movements were analyzed based on the data, and the relationship between the athlete’s FMS test score and sports injury was explored. (1) According to the FMS test results of 18 participants, it was found that the athlete’s total score was the highest at 17 points, with only one person; The minimum score is 7 points, and there is only one person, each accounting for 5% of the total sample size. The highest number of people scored between 11-14, with a total of 13 people, accounting for 72.2% of the total sample size. According to the gold standard for FMS scores, subjects with a total score below 14 are prone to sports injuries, with a total of 9 people, accounting for half of the football team. This indicates that the overall testing level of the team is not high, and the quality of the movements completed in FMS is poor, making the possibility of sports injuries very high. (2) After analyzing the scores of each sub item in the test, it was found that the athletes’ scores in each event were mainly concentrated in 1 and 2 points. The test with the highest score of 3 points was the over the top squat event, which may be due to the fact that this event can reach the standard testing ability after a short period of training. The athletes who scored 2 points in the shoulder flexibility test were the most, which may be due to the fact that team members often engage in shoulder exercises during regular classes, training, and competitions, which improves shoulder flexibility. The test with the highest score of 1 is the trunk rotation stability project, because this test requires particularly high coordination ability, and athletes who have not undergone systematic training find it difficult to maintain limb coordination stability. After investigation, it was found that the functional movement screening scores of male football special athletes from Lvliang College were relatively low. The core stability and control ability of the body, as well as the flexibility of the ankle joint, need to be strengthened. The strength of the quadriceps and rectus femoris muscles needs to be strengthened. Pelvic stability and the flexibility and coordination ability of the lower limb muscles are poor, and the risk of sports injuries is high. In the training after the football team, targeted corrective training should be strengthened, and FMS testing should be used in regular training to reflect the risk of sports injuries and performance of athletes, and to continuously improve the team’s sports level based on this indicator level.